Edukasi Penyakit Malaria pada Ibu Hamil - Melicha Kristine Simanjuntak; Dwi Iryani (Pusat Riset dan Inovasi Nasional, 2022)
Malaria is one of the highest causes of death in the world, including Indonesia. Even though in 2020 there has been a decrease incidence of malaria in Indonesia, several regions in Indonesia, especially the eastern part of Indonesia, are still malaria endemic areas. The Ministry of Health hopes that more areas will become malaria elimination and target Indonesia to be free of malaria by 2030. One of the provinces with a high incidence of malaria is West Papua, especially in the Manokwari Regency area. In 2021, of the 7,628 cases of malaria in West Papua, around 56% will occur in Manokwari Regency. Malaria is a disease that can attack anyone, groups that are more vulnerable and have a severe impact on malaria are pregnant women and children. The purpose of this community service is to provide education to increase pregnant women's knowledge about malaria so that they can carry out prevention and early detection of signs of malaria so that treatment can be carried out before it has a worse impact on pregnancy and the condition of the fetus.